تأثير الصنف وأبعاد الزراعة في نمو وتشكل وإنتاجية رؤوس الملفوف الأحمر - علي, ثراء (Latakia University Journal -Biological Sciences Series, 2018)
This research was conducted in village Gneree in Jablh- Lattakia which located at height of 90 meters above sea level during 2015-2016 on red cabbage) Brassica oleracea var capitata form rubra) on two hybrids Lion F1 and Nile F1 in order to study the effect of plant spacing and variety on growth and formation of red cabbage heads. The completely randomized block design was used with four replications. The study consisted of eight treatments with four different plant spacing for each variety. The indicators of leaf surface area, height, diameter and weight of red cabbage heads, and the total yield were studied. The results showed that variety Nile F1 gave the superior results with significant difference in indicators: leaf surface area, height, diameter and weight of red cabbage heads, and the total yield. Whereas the treatments (70×60), (70×50) gave the superior results with significant difference in indicators: leaf surface area, height, diameter and weight of red cabbage heads. Whereas the treatment (70×30) gave the superior results with significant difference in total yield was respectively (3.28, 2.06) t/d for Nile F1 and Lion F1 نفذ البحث في قرية غنيري التابعة لمدينة جبلة (محافظة اللاذقية) حبث ترتفع القرية 90م عن سطح البحر. أجريت الدراسة على نبات الملفوف الأحمر Brassica oleracea var capitata form rubraحيث استخدم في الدراسة هجينين هما: Lion F1 و Nile F1 خلال الموسم الزراعي 2015-2016 بهدف تحديد أثر الصنف وأبعاد الزراعة في نمو وتشكل رؤوس الملفوف. صممت التجربة وفق تصميم القطاعات العشوائية الكاملة بأربعة مكررات حيث شملت 8 معاملات (4أبعاد مختلفة لكل صنف) بحيث كانت الأبعاد (30×70)، (40×70)، (50×70)، (60×70) ، شملت قراءات التجربة : مساحة المسطح التمثيلي، أبعاد (قطر وارتفاع) ووزن الرؤوس والإنتاجية الكلية. أظهرت النتائج تفوق الصنف Nile F1 على الصنف Lion F1 في مؤشرات مساحة المسطح التمثيلي، قطر وارتفاع ووزن الرؤوس والإنتاجية الكلية في حين أثرت أبعاد الزراعة على نتائج الدراسة فتفوقت معاملتي الزراعة على أبعاد (50×70)، (60×70) على باقي الأبعاد في كلا الصنفين وبفروق معنوية في مؤشرات مساحة المسطح التمثيلي، قطر وارتفاع ووزن الرؤوس بينما أعطت معاملة أبعاد الزراعة (30×70) أعلى إنتاجية كلية متفوقة على معاملات الأبعاد الأخرى بفروق معنوية حيث بلغت 2.06 و 3.28 طن/دونم للصنفين NILE F1, Lion F1 على التوالي.